Functioning of polysemantic words in the mental lexicon of bilinguals - Jumaeva , Kamila (The Lingua Spectrum, 2025)
The article is devoted to the study of the functioning of polysemy in the mental lexicon of bilinguals, which is considered as a complex cognitive and linguistic process. Special attention is paid to the interlingual interaction in the process of actualization of the meanings of polysemantic words, as well as to the cognitive mechanisms that ensure their recognition, storage, processing, and selection in a specific context. The empirical basis of the study is the data from a free association experiment conducted with bilinguals of various levels of language competence. The analysis of the results revealed specific features of the processing of polysemous lexemes in bilinguals compared to monolinguals, including cases of interference, shifts in meanings, and expansion of associative fields. The data obtained demonstrated that in the mental lexicon of bilinguals, the same word is capable of evoking associative responses in both the native and the second language. This fact indicates the presence of close interaction and interpenetration of two language systems in the cognitive structure of a bilingual. It was found that the degree of interlingual influence, the dominant language, and situational conditions play a crucial role in the selection of meanings for polysemous words. The findings expand the understanding of the cognitive structure of the mental lexicon of a bilingual and have practical significance for psycholinguistics, the theory of bilingualism and intercultural communication.